“We All Love Cinderella But...”How Young Nigerian Parents Engage with Portrayals of Women in Disney Animated Films - Chinedu Richard Ononiwu; Chikezie Uzuegbunam (Communicare, 2025)
This study investigated how young Nigerian parents engage with Disney’s portrayals of women in animated films. The study employed a qualitative research approach. Drawing on the Audience Reception Theory and the Parental Mediation Theory, the research examined how these parents interpret and mediate Disney’s gender representations in their parenting practices. Data were collected from 20 university-educated parents, aged 25 to 35 years, across various professions in two diverse urban locations, using a guided snowballing technique. The participants were those who had recent exposure to female portrayals from Disney productions. Findings showed diverse media consumption patterns and a high level of exposure to Disney content. Disney animated films were accessed via a wide variety of platforms such as Disney+, Amazon Prime Video and Disney Channel. Findings also revealed varied interpretations of Disney’s portrayals, including perpetuation of gender stereotypes and depictions of empowerment. In addition, parents employed restrictive, active and co-viewing strategies to mediate these representations. They expressed concerns about gender socialisation and the reinforcement of cultural values. In the young parents’ navigation of negative portrayals through active mediation and restrictive mediation, they questioned and sieved Disney content for their children and also engaged in open communication where they discussed Disney content with their children. They also used the films to teach cultural values. Stay-at-home mothers used these films more than the other groups of parents. This study highlights the relationship between media, culture and parenting in shaping gender attitudes.